Gullibility And Its Effects In the Light Of Prophetic Sunnah - Raed Talal Abdul Qadir Shaat (الإيضاح, 2023)
This research study deals with how folly has been curtailed of any scope to potentially damaging a Muslim society in the light of the relevant sayings of the Prophet. Islam offers comprehensive teachings and thus instructs Muslims to take preemptive measures against any unwise approach.